2017
DOI: 10.1109/tlt.2016.2638811
|View full text |Cite
|
Sign up to set email alerts
|

Point Cloud-Based Automatic Assessment of 3D Computer Animation Courseworks

Abstract: Computer-supported assessment tools can bring significant benefits to both students and teachers. When integrated in traditional education workflows, they may help to reduce the time required to perform the evaluation and consolidate the perception of fairness of the overall process. When integrated within on-line intelligent tutoring systems, they could provide students with a timely feedback and support self-assessment activities. The current work presents an alternative approach (and not just a "yet-another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Sanna et al (2012) present a computer vision and image analysis-based tool for automatic assessment of 3D-modelling exams. Other authors (Lamberti et al, 2014;Paravati et al, 2017) present approaches for automatic assessment of 3D animation assignments.…”
Section: Developments In Automatic Assessmentmentioning
confidence: 99%
“…Sanna et al (2012) present a computer vision and image analysis-based tool for automatic assessment of 3D-modelling exams. Other authors (Lamberti et al, 2014;Paravati et al, 2017) present approaches for automatic assessment of 3D animation assignments.…”
Section: Developments In Automatic Assessmentmentioning
confidence: 99%
“…al. which evaluated 3D animations using point clouds [10]. Paravati's technique sought to train an automated grading algorithm and then compare the algorithm with manual grading by the course instructors.…”
Section: Computational Grading Tools In the Literaturementioning
confidence: 99%
“…Learning using ITS does not require students to be at a physical class location or university space at a specific time [4]. Another advantage of ITS cited by literature is that ITS helps in reducing the grading workload of instructors and, at the same time, mitigate unfair or inconsistent grading [5] It is also important to note that although ITS has many advantages, ITS is more valuable when it is used alongside a human instructor and not when a human instructor is completely replaced [6]. A recent meta-analysis review comprising 50 studies concluded that ITS was beneficial for student learning in 46 out of 50 studies [3].…”
Section: Introductionmentioning
confidence: 99%